Supramolecular Nano-Encapsulation of Anabasine Reduced Its Developmental Toxicity in Zebrafish - Gao, Yan; Yang, Xue; Wang, Ziyi; Zhong, Zhangfeng; Hu, Yuanjia; Wang, Yitao (Frontiers in Chemistry, 2020)
Anabasine (ANA), a major piperidine alkaloid originally isolated from wild tobacco trees (Nicotiana glauca), has been known to induce serious developmental toxicities such as skeletal deformities in livestock and humans. In this study, we thoroughly investigated the supramolecular nano-encapsulations of ANA by an artificial nanocontainer, cucurbit[7] uril (CB[7]), and examined the influences of the nano-encapsulation on ANA’s inherent developmental toxicities on a zebrafish model. We have shown that CB[7] formed 1:1 host-guest inclusion complexes with ANA via a relatively high binding strength (Ka of (7.45 ± 0.31)×104) in an aqueous solution, via UV-vis and 1H nuclear magnetic resonance spectroscopic titrations, as well as isothermal titration calorimetry titration. As a consequence, CB[7] significantly attenuated the developmental toxicity of ANA on zebrafish in vivo. In contrast, for a comparative purpose, β-CD didn’t exert any influence on the toxicity of ANA due to its weak binding with ANA, which was not even measurable via either spectroscopic methods or ITC titration. This is the first head-to-head comparison of this pair of nanocontainers, CB[7] and β-CD, on their potential roles in influencing the toxicity of guest molecules and the results suggested that CB[7] could become a more promising functional excipient for reducing the inherent toxicities of active pharmaceutical ingredients, particularly alkaloids that may form relatively strong host-guest binding species with the host.